HAK HAK PERDATA AKIBAT PERCERAIAN PASANGAN KAWIN SIRRI TERHADAP HARTA BENDA BERSAMA (GONO GINI) - Ali Hadi (IJTIHAD: Jurnal Studi Hukum Islam, 2023)
Indonesian people in general still practice the siri marriage model, namely marriages carried out by a bride and groom who fulfill Islamic requirements, carried out in front of a prince or kiai/Islamic religious figure but are not registered by the Marriage Registrar so they do not yet have the power and legal protection . So that it really has an impact on the position of the assets obtained in the siri marriage period. This sirri marriage case for the community requires an explanation regarding the legal consequences of marriage on the position of marital assets and the efforts that can be made to obtain the rights and obligations of the husband and wife related to marital assets in a siri marriage, so that the public can understand the consequences arising from the sirri marriage and efforts to obtain protection and the force of law in the event of a sharia divorce. Method The research approach used is empirical juridical. The legal materials used are secondary materials in the form of legislation regarding legal consequences for assets arising from unregistered marriages and supported by primary legal materials. Research in the collection of legal materials is carried out through library research. The legal material analysis technique used is qualitative. Siri marriages have negative effects, namely they are not recognized by state law, husbands and wives cannot obtain rights in terms of legal protection for marriages, certainty of the rights and obligations of parents and children cannot be fully protected by law, settlement of the division of assets gono gini in unregistered marriages cannot be resolved based on positive law because the institution or institution does not have the authority to administer the distribution of assets in an unregistered marriage. Siri marriage status is a marriage that does not receive legal protection and services and siri marriage has an impact on the continuity of the household. Only awareness of religious law in society is usually to carry out and fulfill legal rights and obligations to be responsible for realizing the ideals of marriage. The solution that can be taken to be able to obtain legal power and protection is by itsbat nikah.